2023
DOI: 10.3390/ijms24065288
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Metabolisms in Green and White Leaf Sectors of Variegated Pelargonium zonale—An Integrative Transcriptomic and Metabolomic Study

Abstract: The photosynthetically active green leaf (GL) and non-active white leaf (WL) tissues of variegated Pelargonium zonale provide an excellent model system for studying processes associated with photosynthesis and sink-source interactions, enabling the same microenvironmental conditions. By combining differential transcriptomics and metabolomics, we identified the main differences between these two metabolically contrasting tissues. Genes related to photosynthesis and associated pigments, the Calvin–Benson cycle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 81 publications
(166 reference statements)
2
18
0
Order By: Relevance
“…The biphasic response of Phot1 triggered by higher light intensities and blue light of 16 µmol photons m −2 s −1 , with partial chloroplast avoidance preceding the accumulation phase, has been described previously [ 52 , 53 ]. The kinetics obtained in P. zonale leaves can be explained by the fact that both chloroplast accumulation and avoidance occur simultaneously with the avoidance response starting and proceeding faster than the accumulation response, which has a longer lifetime [ 16 , 54 ]. In conclusion, the observed reversible and complex kinetics of T in GS of variegated P. zonale indicated that the interplay between accumulation and avoidance response of chloroplasts is required to maintain their optimal position within the cell in terms of photosynthetic efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biphasic response of Phot1 triggered by higher light intensities and blue light of 16 µmol photons m −2 s −1 , with partial chloroplast avoidance preceding the accumulation phase, has been described previously [ 52 , 53 ]. The kinetics obtained in P. zonale leaves can be explained by the fact that both chloroplast accumulation and avoidance occur simultaneously with the avoidance response starting and proceeding faster than the accumulation response, which has a longer lifetime [ 16 , 54 ]. In conclusion, the observed reversible and complex kinetics of T in GS of variegated P. zonale indicated that the interplay between accumulation and avoidance response of chloroplasts is required to maintain their optimal position within the cell in terms of photosynthetic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, we performed a de novo transcriptome analysis of P. zonale and, for the first time, analysed the differentially expressed genes (DEGs) in GS and WS. Prediction of the subcellular location of a protein encoded by selected DEGs (published in [ 54 ]) was conducted by WoLF-PSORT tool [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the complexity of plant biological processes, transcriptome data cannot accurately describe the macro events occurring in biological systems. In recent years, the combination of metabolomics and transcriptome analyses has been widely used in research conducted in the field to study plants, which can more systematically and comprehensively explore the mechanism of metabolite synthesis [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leaf variegation (e.g., in Pelargonium zonale) has proven to be a suitable model system to study source-sink interactions in terms of carbon and nitrogen allocation within the same leaf under the same microenvironmental conditions [19,20]. These leaves contain photosynthetically inactive white leaf tissue (WL) at the leaf margin and photosynthetically active green leaf tissue (GL) in the leaf centre.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [19], the differential transcriptomic analysis of the gene expression of P. zonale GL and WL under optimal growth conditions was performed for the first time. It was found that the WL tissue had a higher content of nitrogenous compounds, especially free amino acids (AAs), compared to GL.…”
Section: Introductionmentioning
confidence: 99%